2022
DOI: 10.1097/brs.0000000000004468
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transforaminal Endoscopic Discectomy Versus Microendoscopic Discectomy for Lumbar Disc Herniation: 5-year Long-term Results of a Randomized Controlled Trial

Abstract: Study Design. A prospective randomized controlled study. Objective. To compare the efficacy and safety between percutaneous transforaminal endoscopic discectomy (PTED) and microendoscopic discectomy (MED). Summary of Background Data. Two kinds of minimally invasive discectomy, PTED and MED, are now widely used for treating lumbar disk herniation (LDH). The long-term comparative results of these two techniques still remained uncertain. Materials and Methods. In this single-center, open-label, randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Forty-five studies were retrospective, and this was the most prevalent study design. Fourteen studies [3][4][5][10][11][12][13][14][15][16][17][18][19][20] were RCTs.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-five studies were retrospective, and this was the most prevalent study design. Fourteen studies [3][4][5][10][11][12][13][14][15][16][17][18][19][20] were RCTs.…”
Section: Methodsmentioning
confidence: 99%
“…Although PELD causes less damage to paraspinal muscles and posterior spinal elements as compared with MITDS, it has its own set of challenges when it comes dealing with severe calcified disc, migrated disc, large osteophyte, and foraminal stenosis. 30 31 32 33 However, MITDS is a good modality to offer in cases of LDD associated with foraminal stenosis, partially calcified disc, and in cases of obesity. With regard to PELD, MITDS has advantage of three-dimensional view and surgeon familiarity due to the use of operating microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of this study from Guangzhou (China) performed a randomized controlled trial (RCT) to achieve just this by focusing on the five-year clinical and patient-reported outcome measures (PROMs), and the five-year recurrence rate following presentation with a lumbar disc herniation. 1 In this single-centre, open-label RCT, patients were included if they had persistent signs and symptoms of radiculopathy with corresponding imaging-confirmed LDH, and were randomly allocated to the PTED or MED groups. The primary outcome measure selected was the Oswestry Disability Index (ODI) and the secondary outcomes included the Medical Outcomes Study 36-Item Short-Form Health Survey bodily pain (SF-36-BP) and physical function (SF-36-PF), EuroQol five-dimension (EQ-5D) questionnaire, and visual analogue scales for back pain (VAS-back) and leg pain (VAS-leg).…”
Section: Percutaneous Transforaminal Endoscopic Discectomy Versus Mic...mentioning
confidence: 99%